Pencegahan Penyebaran Covid-19 Perspektif Ibn Sina (Analisis Multidimensi Dalam Psikologi Islam) - Arroisi, Jarman; Wulandari, Kartika (UIR Press, 2022)
Covid-19, which originally came from the Wuhan area, China, is an infectious disease outbreak resulting from an outbreak of the SARS-CoV-2 virus. The spread of this virus can be through the air or droplets from an infected person. Prevention that has been attempted at this time is the application of health protocols, quarantine for Covid-19 patients, as well as social distancing. This manuscript seeks to explore the prevention of the spread of COVID-19 through the Islamic tradition with the figure of Ibn Sina. The method used is descriptive-analysis that focuses on literature studies with a qualitative approach that describes Covid-19. Some of the conclusions obtained are in the form of efforts to prevent the spread of infectious diseases at the time of Ibn Sina. First; quarantine. Quarantine is carried out for people with infectious diseases to prevent the spread of disease to healthy people. Second; good food consumption. Consumption of good food can be in the form of nutritious food as well as foods that can prevent the entry of germs in the body, such as garlic. Third; emotional processing. Emotional processing can be done by avoiding fatigue, being patient, thinking positively as well as getting enough sunlight. Fourth; al-wahm al'amil. Al-wahm al 'amil strives to build positive energy in the soul by giving positive perceptions to patients. Fifth; wash with vinegar mixed water. Vinegar water is used to kill microbes that stick to the body and clothes. These 5 efforts to prevent infectious diseases in Ibn Sina's time are very relevant to the current Covid-19 outbreak.